Specific Aspects of Turbulent Flow Separation in Nods and Junctions of Pipelines; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Kharlamov (Harlamov) S. N. Sergey Nikolaevich (Modern Technologies of Oil and Gas Pipelines and Storage Tanks. Process Simulation of Oil and Gas Transportation, 2014)
Title screen